An Analysis of Language Style in A Man Called Otto (2022) Film - Muhammad Mawasy Gery; Muhammad Alim Akbar Nasir (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This research focuses on analyzing the language style used by Otto in the film A Man Called Otto. The researcher used language style theory by Martin Joos who classifies language style into five styles, which are frozen style, formal style, consultative style, casual style and intimate style. This research uses qualitative research as the method and a sociolinguistic approach. In collecting data, the researcher watched and read both film and the transcript, marked the related data, and then collected the data based on theory. The findings indicate that Otto frequently used casual and intimate styles in his interactions, while formal and consultative styles appeared less often. These results suggest that Otto tends to communicate in a more relaxed and personal manner, especially with people he feels close to which can be seen when Otto communicates with his friends who have close relationships with him. But when Otto talks to a person who does not have close relationship with him, he has difficulty expressing what he wants to convey in communication, which causes misunderstanding due to the use of wrong language styles.